Exploring the Perspectives of Middle School Teachers’ Towards Gamification in the EFL Context - Boudour, Ilhem Khadija (Jurnal Arbitrer, 2023)
The current paper looks at investigating middle school teachers’ perspectives towards gamification in the EFL context in Algeria. To this end, the study explores the potential of incorporating digital gamification in EFL teaching with a focus on teachers’ implementation of Gamification in the classroom context. In order to gain a clearer understanding of the phenomenon, the researcher adopted qualitative research using a semi-structured interview. The participants were a total of 11 EFL teachers from various middle schools in Mostaganem – Algeria. The interviewees were selected based on their use of digital technology and game-based teaching methods. The collected data was thematically analyzed using MAXQDA software, employing a descriptive analysis approach. After the analysis, the findings show that teachers frequently incorporate ICT-based and game-based lessons into their teaching practices. Additionally, in accord with their responses, teachers have a clear notion of gamified teaching and learning. However, they lack the necessary expertise to effectively implement gamification. Being a novelty in the arena of language teaching, teachers call for training programs to enable them to effectively incorporate gamification in the EFL classroom. As the study concludes, it provides a clear understanding of the teachers’ standpoint regarding gamification, their openness, and readiness to adopt modern teaching methods. It also offers valuable insights into state-of-the-art teaching methods and paves the way for further considerations in gamified lesson design.